Defining Culture Conditions for the Hidden Nitrite-Oxidizing Bacterium Nitrolancea - Spieck, Eva; Sass, Katharina; Keuter, Sabine; Hirschmann, Sophia; Spohn, Michael; Indenbirken, Daniela; Kop, Linnea F. M.; Lücker, Sebastian; Giaveno, Alejandra (Frontiers in Microbiology, 2020)
Nitrification is a key process for N-removal in engineered and natural environments, but recent findings of novel nitrifying microorganisms with surprising features revealed that our knowledge of this functional guild is still incomplete. Especially nitrite oxidation – the second step of nitrification – is catalyzed by a phylogenetically diverse bacterial group, and only recently bacteria of the phylum Chloroflexi have been identified as thermophilic nitrite-oxidizing bacteria (NOB). Among these, Nitrolancea hollandica was isolated from a laboratory-scale nitrifying bioreactor operated at 35°C with a high load of ammonium bicarbonate. However, its distribution remains cryptic as very few closely related environmental 16S rRNA gene sequences have been retrieved so far. In this study, we demonstrate how such thermophilic NOB can be enriched using modified mineral media inoculated with samples from a wastewater side-stream reactor operated at 39.5°C. Distinct cultivation conditions resulted in quick and reproducible high enrichment of two different strains of Nitrolancea, closely related to Nl. hollandica. The same cultivation approach was applied to a complex nitrite-oxidizing pre-enrichment at 42°C inoculated with biomass from a geothermal spring in the Copahue volcano area in Neuquen, Argentina. Here, an additional distinct representative of the genus Nitrolancea was obtained. This novel species had 16S rRNA and nitrite oxidoreductase alpha subunit (nxrA) gene sequence identities to Nl. hollandica of 98.5% and 97.2%, respectively. A genomic average nucleotide identity between the Argentinian strain and Nl. hollandica of 91.9% indicates that it indeed represents a distinct species. All Nitrolancea cultures formed lancet-shaped cells identical to Nl. hollandica and revealed similar physiological features, including the capability to grow at high nitrite concentrations. Growth was optimal at temperatures of 35 - 37°C and was strongly enhanced by ammonium supplementation. Genomic comparisons revealed that the four Nitrolancea strains share 2399 out of 3387 orthologous gene clusters and encode similar key functions. Our results define general growth conditions that enable the selective enrichment of Nitrolancea from artificial and natural environments. In most natural habitats these NOB apparently are of low abundance and their proliferation depends on the balanced presence of nitrite and ammonium, with an optimal incubation temperature of 37°C.